Pengaruh Return On Asset (ROA), Return On Equity (ROE) terhadap Pertumbuhan Laba dengan Good Corporate Governance Sebagai Variabel Pemoderasi (Studi Perusahaan Food and Beverages yang terdaftar di BEI Periode Tahun 2015-2018) - Novita Wulan Dari; Budi Wahono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract It was a quantitative type of study, by utilizing a secondary data such as the company annual financial reports. There were 11 companies became the samples of this company food and beverages in Indonesia listed in the Indonesian Stock Exchane, which were determined based on the purposive sampling technique during the periode of 4 years from 2015 until 2018. The results indicated that (1) the return on asset had an effect negatif on the growth profits but the return on equity had an effect positif on the growth profits, (2) the good corporate governance not could modernize return on asset and return on equity on the growth profits to a negative direction.Keywords: Return On Asset, Return On Equity, Good Corporate Governance, Growth Profits.